Prevalence and predictors of anaemia in pregnancy: the role of birth spacing, educational status and awareness levels in Meerut City - Kumar, Prem; Ahmad, Sartaj; Davey, Anuradha; Saxena, Komal (International Journal Of Community Medicine And Public Health, 2026)
Background: Anaemia during pregnancy remains a major public health challenge in India and is a leading contributor to maternal and neonatal morbidity. Understanding its determinants is essential for designing targeted interventions. Evidence from urban areas such as Meerut City is limited, despite rapid urbanisation and shifting socioeconomic patterns. To assess the prevalence and predictors of anaemia among pregnant women in Meerut City, with specific focus on birth spacing, educational status and awareness related to anaemia. Methods: A cross-sectional study was conducted among 904 pregnant women attending antenatal clinics in Meerut City. Data were collected using a structured, interviewer-administered questionnaire along with haemoglobin estimation based on WHO criteria. Logistic regression analysis was performed to identify significant predictors of anaemia. Results: Anaemia prevalence was 59.6%, comprising 22.9% mild, 34.5% moderate and 2.2% severe cases. Short interpregnancy interval (<24 months) showed a strong association with anaemia (p<0.05). Women with lower educational attainment and poor awareness of anaemia were significantly more likely to be anaemic, indicating a prominent role of reproductive, educational and informational factors. Conclusions: Anaemia among pregnant women in Meerut City remains alarmingly high. Short birth spacing, low maternal education and inadequate awareness emerged as key predictors. Strengthening ANC counselling, enhancing women’s health literacy and promoting optimal birth spacing are critical strategies to reduce the burden of anaemia in similar urban populations.